Analysis of Olympic Games (Rio de Janeiro, 2016) participants` individual competition compositions in calisthenics - Kovalenko, Y. O.; Boloban, V. N. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2017)
Purpose: to show structural elements of individual competition compositions of female gymnasts - Olympic Games (Rio de Janeiro, 2016) finalists. Material: video-computer analysis of Olympic Games participants` exercises; analysis of competition records. Results: it was found that female gymnasts` individual fitness is characterized by the following: correlation of time for Body Difficulty elements` fulfillment and Apparatus Difficulty elements. It is expressed in quickness of preparation to element`s fulfillment; in logical and technically accurate transition from element to element. Accent on static elements permitted for sportswomen to reduce movements` area. With dynamic style of elements` fulfillment movements` area was larger. Conclusions: Most female gymnasts demonstrated natural elements` distribution in compositions. Space movements opened the best views of static and dynamic elements` fulfillment that was an evidence of female gymnasts` high sportsmanship.